Minimally invasive treatment of both-column acetabular fractures through the Stoppa combined with iliac fossa approach - Ruipeng Zhang (Nature Portfolio, 2017)
Abstract Both-column fractures are the most complicated group of acetabular fractures. Although great progress of surgical technique has been made, the choice of approach is controversial. All the fragments could be exposed and managed through combined ilioinguinal and Kocher-Langenbeck (IL+KL) approaches, which has been widely used to conduct the both-column fractures. However, the clinical popularization may be restricted for high rate of complication. Most internal area of the hemipelvis could be exposed through Stoppa combined with iliac fossa (S+IF) approach. The majority of both-column fractures were managed through IL+KL approaches or S+IF approach in our institution. The comparison of the two surgical methods was done in this study. The purpose is to examine whether S+IF approach could achieve the satisfactory reduction and fixation for both-column fractures.